Two-phase unsteady flow in solid rocket motors - Dupays, Joël (Aerospace science and technology, 2002)
Aluminized propellants are frequently used in solid rocket motors to increase specific impulse. Unlike the other ingredients, aluminum particles can burn in a significant portion of the chamber and produce a condensed phase that is carried out into the flowfield. Thereby, aluminum particles can affect appreciably combustion instabilities by acting as driving or, on the contrary, as damping mechanisms. Therefore, a reliable stability prediction must include the description of the reactive two-phase flow in the motor. Studies realized on this subject in the ASSM program are reviewed. Les propergols aluminisés sont fréquemment utilisés dans les moteurs à propergol solide pour augmenter l'impulsion spécifique. Contrairement aux autres ingrédients du propergol, les particules d'aluminium peuvent brûler dans une portion significative de la chambre et produire une phase condensée qui est transportée dans l'écoulement. De ce fait, les particules d'aluminium peuvent modifier sensiblement les instabilités de combustion en les amplifiant ou, au contraire, en les réduisant. C'est pourquoi, une prédiction fiable de la stabilité doit inclure la description de l'écoulement diphasique dans le moteur. Les études réalisées sur ce sujet dans le programme ASSM sont présentées.